A Negotiation Model for Concurrent Engineering - Coutinho, C.; Cretan, A.; Jardim-Goncalves, R. (Proceedings of the 7th International Systems & Concurrent Engineering for Space Applications Conference (SECESA 2016), 2016)
The Concurrent Engineering (CE) concept is all about interoperability, about the capture of business requirements, and their fragmentation into multiple discipline views and parameters. The CE implementation is then followed by a set of interoperations between the multiple interested stakeholders - which are done concurrently - with the single purpose of reaching the best decision in the most optimised amount of time. Within this process, numerous decisions are taken, some that are more correct than others. If the iterative set of interoperations between the experts from multiple disciplines fails to reach a conclusion, it is quite difficult to understand the trend of decisions that led to the failure, or in the same manner, the one that leads to success. It would be important then to have on the CE environment a mechanism that is able to capture and formalise for each decision the set of data, evidences and opinions that supported it, as well as enumerating (the most relevant) alternatives that might be used instead. This paper proposes a negotiation model that aims to capture the negotiation steps that are taken towards reaching CE decisions, providing field for the future analysis of alternatives and improvements. This model is being implemented in the H2020 C2NET project for supporting manufacturing.